Numerical simulation and experimental study of root anchorage /Abdolhossein Khalilnejad - Abdolhossein, Khalilnejad (2013)
Understanding the mechanism of root anchorage in soil slope is important in order to study the effects of vegetation roots on land sliding, especially in the subtropical and tropical areas with the dense herb coverage. A generic 3D finite element model has been widely used in recent years to characterize the anchorage mechanisms by the pulling out where each component of the anchorage can be tested individually. Despite the common usage of finite element simulation, few restrictions are causing inaccuracy in simulation result. To overcome those restrictions, in this research the root system was simulated and alternative root soil interaction was evaluated. In order to achieve a better understanding of pulling out effect on soil, the Mises stress and logarithmic strain distribution curve was studied. The effect of root architect and soil parameters such as soil cohesion and soil friction angle using improved root model were also examined. Simulation during this study was carried out using FEM software ABAQUS 6.10.ef and analysis method chosen was Explicit (semi static) method. To achieve the comparable result to reality, the root and soil mechanical properties were identified and measured during laboratory tests and pulling out process for Melastoma malabathricum. Based on the experimental results, the uplifting force is higher for plants with higher root volumes and thicker lateral roots. According to the simulation results, it is found that the distribution of Mises stress and logarithmic strain in soil is highly dependent on the depth and width range of the roots. The main factor affecting the Mises stress and the logarithmic strain distribution is the rooting length and root geometry. The concentrations and amount of stress were more apparent in the model with long taproot. In the process of changing in root architecture, it appears that the most insistent root architecture against the pull out is the root with branches of horizontal deviation angel that is equal to 53. By changing the soil properties, it is discovered that the friction angle is affecting roots pull out capacity even with small root inclination angle. The pull out resistance increases with increasing friction angle. In the case of changing the soil cohesion, it is found that the soil cohesion value denotes direct proportion to root anchorage. However, in soil with higher plasticity as CH (fat clay), the effect of soil cohesion is the maximum with the increase of the silt content. With the reduction of plasticity, the soil cohesion effect also decreases. In conclusion, this study discovered that during the pulling out, Mises stress and consequently logarithmic strain distribution are more concentrated on root and soil effect is limited to almost 25% of final displacement. Therefore, the root architecture such as long taproot, root pattern and root branches deviation angle, playing more important role than soil characteristics such as soil cohesion and soil friction angle. Validation of the simulation result was carried out by comparing the simulation result with experimental pull out result and also with those in well control laboratory test.